Achievement goals and goal progress as drivers of work engagement - Bipp, Tanja; Kleingeld, Ad; Schelp, Leonie (Psychological reports, 2021)
In two studies, we investigated the role of self-regulatory behavior in terms of achievement goals and goal progress for work engagement. Study 1 (N = 205) revealed that trait learning goals were positively related to work engagement and performance-approach and performance-avoidance goals were unrelated to work engagement. In a second study, employees were asked to either set a (state) learning, performance-approach, or performance-avoidance goal for the upcoming work week. Goal progress and work engagement were measured one week later (N = 106). Learning goals at the trait and state level were associated with higher work engagement and performance-avoidance goals were unrelated to work engagement. We found a positive relationship of goal progress with work engagement, in particular for employees who pursued learning or performance-approach goals. Our studies contribute to theory building by delineating the (combined) role of goal orientations (trait), state achievement goals, and goal progress for work engagement, as well as generating practical implications for the design of effective interventions to enhance work motivation in organizational practice.
Zuerst online publiziert: 23. September 2020
Gesehen am 05.09.2025